PENGARUH KOMPENSASI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA GTT SMA NEGERI DI KABUPATEN KLATEN - Handayani, Trisnawati L.D. (2005)
The objective of this research is to investigate the influences of compensation, motivation and work environment to performance of State High School honorer teachers in Klaten Regency. The samples comprise of 50 respondents, collected using purposive sampling. This research used questionnaire as research instrument and regression analysis to investigate the influence between independents and dependent variables. Based on literature reviews, this research hypothesized that compensation, motivation and work environments influence positively to performance. The results of this research show that compensation doesn’t influence performance, while motivation and work environment influence positively to performance. These suggest that changes in compensation will not influence performance, while changes in motivation and work environment will influence performance positively. This research imply that to increase teacher’s performance , the Chief of High School should increase motivation and work performance. Motivation could be increased using personal approach, maintain as a family, apply innovative learning model, and esteem the outstanding teachers. Work environment could be increased by making clean the school environment including the toilet, do not put the trash everywhere, enough lighting, good ventilation, decrease smoke pollution, and harmonized honorer teachers and the others.